KEPEMIMPINAN KEPALA SEKOLAH DALAM PEMANFAATAN RAPOR PENDIDIKAN UNTUK MENINGKATKAN MUTU SEKOLAH DASAR - Yuyun Yuningsih; Eva Dianawati Wasliman (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Improving the quality of primary schools requires principals to optimally use data in planning, implementing, evaluating, and following up school improvement programs. The Educational Report Card (Rapor Pendidikan) developed by the Ministry of Education provides a comprehensive picture of students’ learning outcomes, learning processes, school climate, and school management, and therefore has the potential to become the basis for data-based planning at the school level. However, preliminary findings at SDN Malabenghar indicated that the principal had not yet fully utilized the Educational Report Card as an instrument for diagnosis and decision making, so that quality improvement programs were not always directed at the identified root problems. This study aims to analyze principal leadership in utilizing the Educational Report Card to improve the quality of primary schools at SDN Malabenghar, focusing on four aspects: planning, implementation, evaluation, and follow-up. The research employed a qualitative approach with a case study method. Data were collected through observation, in-depth interviews with the principal and teachers, and documentation study of planning documents, reports, and the school’s Educational Report Card. Data were analyzed descriptively by reducing, presenting, and drawing conclusions from emerging patterns within the case context. The findings show that the principal has begun to develop more systematic planning based on the Educational Report Card by analyzing priority indicators, determining improvement focus, formulating goals, and integrating programs into medium- and annual-term school plans. In the implementation stage, the principal acts as an instructional and transformational leader by communicating the importance of data, mobilizing teachers in literacy and numeracy programs, and conducting supervision based on Report Card findings. Evaluation is carried out through regular monitoring, joint reflection with teachers, and re-using data to review progress, although documentation remains inconsistent. Follow-up is evident in program adjustment, teacher capacity building, and integration of evaluation results into subsequent planning. Overall, the use of the Educational Report Card at SDN Malabenghar shows a positive trend but still requires strengthening of data literacy, documentation culture, and consistency in implementing continuous improvement cycles. BSTRAK Peningkatan mutu sekolah dasar menuntut kepala sekolah mengoptimalkan pemanfaatan data mulai dari perencanaan, pelaksanaan, evaluasi, hingga tindak lanjut. Rapor Pendidikan yang dikembangkan Kemendikbudristek menyajikan gambaran komprehensif capaian hasil belajar, proses pembelajaran, iklim belajar, dan tata kelola sekolah, sehingga berpotensi menjadi dasar perencanaan berbasis data. Namun, temuan awal di SDN Malabenghar menunjukkan bahwa pemanfaatan Rapor Pendidikan oleh kepala sekolah belum optimal sebagai instrumen diagnosis dan pengambilan keputusan, sehingga program peningkatan mutu belum sepenuhnya menyasar akar masalah. Penelitian ini bertujuan mengkaji kepemimpinan kepala sekolah dalam memanfaatkan Rapor Pendidikan untuk meningkatkan mutu sekolah dasar di SDN Malabenghar, dengan fokus pada aspek perencanaan, pelaksanaan, evaluasi, dan tindak lanjut. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus. Data dikumpulkan melalui observasi, wawancara mendalam dengan kepala sekolah dan guru, serta telaah dokumen perencanaan, pelaporan, dan Rapor Pendidikan. Analisis data dilakukan secara deskriptif melalui reduksi, penyajian, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa kepala sekolah telah mulai menerapkan perencanaan berbasis Rapor Pendidikan secara sistematis melalui analisis indikator prioritas dan integrasi program ke dalam RKJM, RKS, dan RKAS. Pelaksanaan ditunjukkan melalui peran kepemimpinan instruksional dan transformasional, evaluasi melalui monitoring dan refleksi, serta tindak lanjut berupa penyesuaian program. Secara umum, pemanfaatan Rapor Pendidikan menunjukkan tren positif, namun masih memerlukan penguatan literasi data, dokumentasi, dan konsistensi perbaikan berkelanjutan.